Fetal hemoglobin modifies the disease manifestation of severe Plasmodium falciparum malaria in adult patients with sickle cell anemia. - Prasanta Purohit (Mediterranean Journal of Hematology and Infectious Diseases, 2016)
Sickle cell anemia (SCA) and Plasmodium falciparum malaria are two major public health problems in the state of Odisha, India. The prevalence of sickle cell gene in the western part of Odisha is 13.1%,1P. falciparum contributes 23% of cases and 15% of malaria-related deaths in India. Various......